Peran Guru PAI dalam Mengembangkan Literasi Keagamaan Peserta Didik di Era Digital - Jazlina, Nurul; Sabila, Nur; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The role of Islamic Religious Education (PAI) teachers in developing students’ religious literacy in the digital era is highly important and strategic. PAI teachers are not only responsible for delivering learning materials, but also act as facilitators, motivators, and mentors in shaping religious understanding that is critical, contextual, and relevant to the development of information technology. The digital era presents both challenges and opportunities, as students can easily access various religious information through social media, websites, and digital applications. However, without proper guidance, such information may lead to misunderstandings or even radicalism. Therefore, PAI teachers are required to integrate technology-based learning methods, teach digital literacy skills, and instill the values of religious moderation so that students are able to select, comprehend, and internalize Islamic teachings wisely. Thus, the role of PAI teachers in the digital era is not limited to knowledge transfer, but also to building religious character that is adaptive to the dynamics of the times.